Letter: Collections for Spain - Edwards, Ebby
028-0096-001 TELEPHONE: MUSEUM 8886 TELEGRAMS: MINFEDBRIT, WESTCENT, LONDON THE MINEWORKERS' FEDERATION OF GREAT BRITAIN 50, Russell Square, London, W.E.1. 18th January, 1937. SECRETARY: EBBY EDWARDS H. V. Tewson, Esq., T.U.C., Transport House, Smith Square , S.W.1. Dear Mr. Tewson, Collections for Spain. I thank you for your letter of the 16th inst., contents of which are duly noted. Yours sincerely, Ebby Edwards, Secretary. 292/946/28/96